Cellulose-based aerogel with dynamic adjustable electromagnetic wave absorption performance and preparation method thereof
Cellulose-based aerogels were prepared by physical ice crystal extrusion and multiple freeze-drying processes. Combined with conductive/magnetic functional components, the problem of the inability to dynamically adjust the electromagnetic wave absorption characteristics of existing aerogel materials was solved. Dynamic control of electromagnetic wave absorption performance under different strain amplitudes was achieved, making it suitable for smart devices and military equipment.
Patent Information
- Application Number
- CN202510993282.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-11-28
AI Technical Summary
Existing cellulose-based aerogel electromagnetic wave absorbing materials can only operate in specific electromagnetic wave frequency bands, making it difficult to adjust their electromagnetic wave absorption characteristics according to the needs of different scenarios.
Cellulose nanofibers are assembled into microfibers by physical ice crystal extrusion and mixed with conductive/magnetic functional components. Cellulose-based aerogels are prepared by multiple freeze-drying processes, and the electromagnetic wave absorption performance is modulated by controlling the strain amplitude.
Dynamically tunable electromagnetic wave absorption properties of cellulose-based aerogels have been achieved, which can significantly change the electromagnetic wave absorption properties under different strain amplitudes, covering multiple electromagnetic wave frequency bands, and are suitable for smart devices and military applications.
Smart Images

Figure BDA0005506527180000111
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of electromagnetic wave absorbing material design and preparation, and particularly relates to a cellulose-based aerogel with dynamically adjustable electromagnetic wave absorbing performance and a preparation method thereof. BACKGROUND
[0002] The rapid development of modern electromagnetic wave transmission technology has greatly enhanced the development of weather detection, navigation and communication technology of various frequency bands, but also has led to serious problems including electromagnetic interference, privacy leakage and health problems caused by long-term exposure. In recent years, cellulose-based aerogel electromagnetic wave absorbing materials based on new nanomaterials have made great progress. By adjusting the functional material composition in the cellulose-based aerogel and combining multiple synergistic electromagnetic loss mechanisms, effective absorption of electromagnetic waves of specific frequency bands can be achieved. For example, CN119012665A discloses a preparation method of a bamboo fiber-based electromagnetic wave absorbing material, which realizes effective absorption of electromagnetic waves at 14.08GHz by optimizing the content of aniline and graphene oxide. In addition, CN118165360A discloses a preparation method of cellulose-assisted double-crosslinked magnetic MXene composite aerogel, and finally achieves strong electromagnetic wave absorbing performance of -63.9dB and -44.8dB at 1.7mm, 15.7GHz and 3mm, 8.5GHz, respectively. However, these existing reported aerogel electromagnetic wave absorbing materials can only work at specific electromagnetic wave frequency bands, and it is difficult to adjust their electromagnetic wave absorbing characteristics according to real-time scene requirements, which cannot meet the dynamic requirements of electromagnetic wave absorbing performance (RL) of intelligent devices and military applications. SUMMARY
[0003] [TECHNICAL PROBLEM]
[0004] The electromagnetic wave absorbing aerogel material can only work at specific electromagnetic wave frequency bands, and it is difficult to adjust its electromagnetic wave absorbing characteristics according to the scene requirements.
[0005] [TECHNICAL SCHEME]
[0006] The purpose of the present application is to provide a cellulose-based aerogel with dynamically adjustable electromagnetic wave absorbing performance. First, cellulose nanofibers are assembled into cellulose microfibers by physical ice crystal extrusion, and then conductive / magnetic paths are built by adding functional components. The preparation process and composition of the cellulose-based aerogel are optimized to construct a cellulose-based aerogel with excellent elastic performance, realize adjustable electromagnetic characteristics under strain amplitude driving, and achieve dynamically adjustable electromagnetic wave absorbing performance. The present application solves the problem that the traditional electromagnetic wave absorbing aerogel material can only work at specific electromagnetic wave frequency bands, and it is difficult to adjust its electromagnetic wave absorbing characteristics according to the scene requirements.
[0007] The application provides a method for regulating electromagnetic wave absorption performance of a material by controlling strain amplitude of the material, which comprises the following steps: mixing a cellulose microfiber dispersion liquid with an electrically conductive / magnetically conductive functional component, completely freezing, and then performing second freeze drying to obtain a cellulose-based aerogel; and then controlling the strain amplitude of the cellulose-based aerogel to regulate the electromagnetic wave absorption performance.
[0008] In an embodiment of the application, the method specifically comprises the following steps:
[0009] (1) completely freezing a cellulose nanofiber dispersion liquid, and then performing freeze drying to obtain cellulose microfibers; dispersing the obtained cellulose microfibers in deionized water to obtain a cellulose microfiber dispersion liquid;
[0010] (2) mixing an electrically conductive / magnetically conductive functional component with the cellulose microfiber dispersion liquid to form a mixed dispersion liquid, completely freezing, and then performing second freeze drying to obtain a cellulose-based aerogel;
[0011] (3) controlling the strain amplitude of the cellulose-based aerogel to regulate the electromagnetic wave absorption performance.
[0012] The application further provides a preparation method of a cellulose-based aerogel with dynamically adjustable electromagnetic wave absorption performance, which comprises the following steps:
[0013] (1) completely freezing a cellulose nanofiber dispersion liquid, and then performing freeze drying to obtain cellulose microfibers; dispersing the obtained cellulose microfibers in deionized water to obtain a cellulose microfiber dispersion liquid;
[0014] (2) cellulose-based aerogel preparation: mixing an electrically conductive / magnetically conductive functional component with the cellulose microfiber dispersion liquid, diluting, forming a mixed dispersion liquid, completely freezing, and then performing second freeze drying to obtain a cellulose-based aerogel.
[0015] In an embodiment of the application, the cellulose nanofiber in step (1) is obtained by one or more of TEMPO oxidation method and mechanical grinding process and is derived from one or more of bleached coniferous wood, broad-leaved wood and bamboo pulp, cotton pulp and hemp fiber.
[0016] In an embodiment of the application, the cellulose nanofiber in step (1) has any one of the following surface functional groups: carboxyl, amino and phosphoric acid group.
[0017] In an embodiment of the application, the cellulose nanofiber in step (1) has a diameter of 5-50 nm and a length of 10-100 μm.
[0018] In one embodiment of the present invention, the concentration of the cellulose nanofiber dispersion in step (1) is 0.05 wt.% to 0.5 wt.%.
[0019] In one embodiment of the present invention, the freezing temperature in step (1) is -196°C to -20°C. Further options include -196°C to -40°C.
[0020] In one embodiment of the present invention, the freeze-drying conditions in step (1) are a cold well temperature of -40°C and a pressure of 10Pa.
[0021] In one embodiment of the present invention, the concentration of the cellulose microfiber dispersion in step (1) is 0.05 wt.% to 2 wt.%. Specifically, 1 wt.% may be selected.
[0022] In one embodiment of the present invention, the conductive functional component in step (2) is one or more of carbon black, carbon quantum dots, carbon nanotubes, MXene, graphene, fullerene, and nanometals. Specifically, silver nanowires may be selected.
[0023] In one embodiment of the present invention, the magnetically conductive functional component in step (2) is one or more of ferrite, metallic magnetic alloy, metallic nanoparticles, magnetic oxide nanoparticles, and topological insulators. Specifically, carbonyl iron powder may be selected.
[0024] In one embodiment of the present invention, the conductive / magnetic functional component in step (2) has a mass ratio of 1 wt.% to 50 wt.% relative to the microfibers in the solution. Specifically, 30 wt.% is optional.
[0025] In one embodiment of the present invention, the concentration of cellulose microfibers in the mixed dispersion in step (2) is 0.1 wt.% to 2 wt.%. Specifically, 0.2 wt.% is optional.
[0026] In one embodiment of the present invention, the mixing method in step (2) is one or more of cell pulverization, ultrasonication, and mechanical grinding.
[0027] In one embodiment of the present invention, the freezing temperature in step (2) is -196°C to -40°C.
[0028] In one embodiment of the present invention, the freeze-drying conditions in step (2) are: a cold well temperature of -40°C and a pressure of 10 Pa.
[0029] This invention provides a cellulose-based aerogel with dynamically tunable electromagnetic wave absorption properties prepared based on the above method.
[0030] The present invention also provides the application of the above-mentioned cellulose-based aerogel in smart devices.
[0031] The present invention also provides the application of the above-mentioned cellulose-based aerogel in military equipment.
[0032] The present invention also provides the application of the above-mentioned cellulose-based aerogel in the field of mobile communications.
[0033] The beneficial effects of this invention are:
[0034] This invention provides a cellulose-based aerogel with dynamically adjustable electromagnetic wave absorption properties under strain-driven conditions and its preparation method. The cellulose-based aerogel with excellent elastic properties is prepared by physical ice crystal extrusion and multiple freeze-drying. By changing different strain amplitudes, the porosity and dielectric / magnetic properties of the cellulose-based aerogel are controlled, thereby achieving dynamic changes in the working frequency band of the electromagnetic wave absorbing aerogel material. Detailed Implementation
[0035] The following examples further illustrate the outstanding advantages and significant features of the present invention. These examples are for illustrative purposes only and are not intended to limit the scope of the invention.
[0036] The testing method is analyzed in detail below:
[0037] (1) Compression resilience
[0038] The compressive stress-strain curves of the samples in the examples and comparative examples were tested using a universal testing machine, with strain amplitudes of 20%, 40%, 60%, and 80%, respectively, and the strain loss was calculated.
[0039] (2) Electromagnetic wave absorption performance
[0040] Electromagnetic parameters of the samples in the examples and comparative examples were tested according to the test methods specified in GJB / Z 158-2011 and GJB 5792-2006, and the electromagnetic wave absorption performance under different strain amplitudes was calculated.
[0041] Example 1
[0042] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.05 wt.% cellulose nanofiber dispersion, and then completely frozen at -196℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0043] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0044] (3) Add silver nanowires with a weight ratio of 30 wt.% of cellulose microfibers to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse them into a uniform mixed dispersion. Then, further dilute with water to obtain a mixed dispersion with a cellulose microfiber concentration of 0.2 wt.%.
[0045] (4) The mixed dispersion obtained in step (3) is completely frozen at -40°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0046] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0047] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 1). The cellulose-based aerogel exhibited excellent elastic properties and almost no strain loss at different strain amplitudes. Furthermore, the electromagnetic wave absorption performance of this cellulose aerogel material can be dynamically adjusted based on the strain amplitude. The electromagnetic wave absorption performance varies significantly at different strain amplitudes, and the frequency at which the best electromagnetic wave absorption performance is obtained covers multiple electromagnetic wave frequency bands.
[0048] Table 1. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0049] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 0 0.2 0.4 0.7 0.9 Optimum RL (-dB) 8 40 65 32 16 Corresponding frequency (GHz) 5 8 11 14 17
[0050] Example 2
[0051] Example 2 differs from Example 1 in that the temperature of the first complete freezing step (1) is changed, while everything else remains the same:
[0052] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.05 wt.% cellulose nanofiber dispersion, and then completely frozen at -40℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0053] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0054] (3) Add silver nanowires with a weight ratio of 30 wt.% of cellulose microfibers to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse them into a uniform mixed dispersion. Then further dilute to obtain a mixed dispersion with a cellulose microfiber concentration of 0.2 wt.%.
[0055] (4) The mixed dispersion obtained in step (3) is completely frozen at -40°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0056] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0057] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 2). The cellulose-based aerogel exhibited excellent elastic properties, with slight strain loss at different strain amplitudes, and significant differences in electromagnetic wave absorption performance at different strain amplitudes. The frequency range at which the optimal electromagnetic wave absorption performance was obtained covered multiple electromagnetic wave bands. However, its dynamic adjustability based on strain amplitude was slightly weaker than that of Example 1.
[0058] Table 2. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0059] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 0 5 7 10 15 Optimum RL (-dB) 6 31 55 36 22 Corresponding frequency (GHz) 4 7 10 15 17
[0060] Example 3
[0061] Example 3 differs from Example 1 in that the concentration of cellulose microfibers in the mixed dispersion in step (3) is changed, while other aspects remain the same:
[0062] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.05 wt.% cellulose nanofiber dispersion, and then completely frozen at -196℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0063] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0064] (3) Add silver nanowires with a weight ratio of 30 wt.% of cellulose microfibers to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse them into a uniform mixed dispersion. Then further dilute to obtain a mixed dispersion with a cellulose microfiber concentration of 0.4 wt.%.
[0065] (4) The mixed dispersion obtained in step (3) is completely frozen at -40°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0066] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0067] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 3). The cellulose-based aerogel exhibited good elastic properties, with low strain loss at different strain amplitudes. The electromagnetic wave absorption performance showed significant differences at different strain amplitudes, and the frequency range at which the optimal electromagnetic wave absorption performance was obtained covered multiple electromagnetic wave bands. However, its dynamic adjustability based on strain amplitude was weaker than that of Example 1.
[0068] Table 3. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0069] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 0 10 16 21 27 Optimum RL (-dB) 3 22 41 28 17 Corresponding frequency (GHz) 5 8 10 11 13
[0070] Example 4
[0071] Example 4 differs from Example 1 in that the proportion of conductive filler in the mixed dispersion in step (3) is changed, while other aspects remain the same:
[0072] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.05 wt.% cellulose nanofiber dispersion, and then completely frozen at -196℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0073] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0074] (3) Add silver nanowires with a weight ratio of 50 wt.% of cellulose microfibers to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse them into a uniform mixed dispersion. Then further dilute to obtain a mixed dispersion with a cellulose microfiber concentration of 0.2 wt.%.
[0075] (4) The mixed dispersion obtained in step (3) is completely frozen at -40°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0076] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0077] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 4). The cellulose-based aerogel exhibited good elastic properties, with low strain loss at different strain amplitudes. The electromagnetic wave absorption performance showed significant differences at different strain amplitudes, and the frequency range at which the optimal electromagnetic wave absorption performance was obtained covered multiple electromagnetic wave bands. However, its dynamic adjustability based on strain amplitude was significantly weaker than that of Example 1.
[0078] Table 4. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0079] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 0 7 15 27 34 Optimum RL (-dB) 8 32 27 15 6 Corresponding frequency (GHz) 3 6 8 10 13
[0080] Example 5
[0081] Example 5 differs from Example 1 in that the dilution concentration of the cellulose nanofiber dispersion in step (1) is changed, while other aspects remain the same:
[0082] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.2 wt.% cellulose nanofiber dispersion, and then completely frozen at -196℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0083] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0084] (3) Add silver nanowires with a weight ratio of 30 wt.% of cellulose microfibers to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse them into a uniform mixed dispersion. Then further dilute to obtain a mixed dispersion with a cellulose microfiber concentration of 0.2 wt.%.
[0085] (4) The mixed dispersion obtained in step (3) is completely frozen at -40°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0086] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0087] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 5). The cellulose-based aerogel exhibited good elastic properties, with low strain loss at different strain amplitudes. The electromagnetic wave absorption performance showed significant differences at different strain amplitudes, and the frequency range at which the optimal electromagnetic wave absorption performance was obtained covered multiple electromagnetic wave bands. However, its dynamic adjustability based on strain amplitude was slightly weaker than that of Example 1.
[0088] Table 5. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0089] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 0 8 11 15 20 Optimum RL (-dB) 5 33 55 42 12 Corresponding frequency (GHz) 6 8 11 15 18
[0090] Example 6
[0091] Example 6 differs from Example 1 in that the type of conductive / magnetic functional component in step (3) is changed, while other aspects remain the same:
[0092] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.2 wt.% cellulose nanofiber dispersion, and then completely frozen at -196℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0093] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0094] (3) Add carbonyl iron powder with a weight ratio of 30 wt.% of cellulose microfiber to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse it into a uniform mixed dispersion. Then further dilute it to obtain a mixed dispersion with a cellulose microfiber concentration of 0.2 wt.%.
[0095] (4) The mixed dispersion obtained in step (3) is completely frozen at -40°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0096] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0097] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 6). The cellulose-based aerogel exhibited excellent elastic properties, with almost no strain loss at different strain amplitudes, and significant differences in electromagnetic wave absorption performance at different strain amplitudes. The frequency range at which the optimal electromagnetic wave absorption performance was obtained covered multiple electromagnetic wave bands. However, its dynamic adjustability based on strain amplitude was weaker than that of Example 1.
[0098] Table 6. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0099] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 0.2 0.4 0.7 0.9 1.3 Optimum RL (-dB) 4 24 45 29 18 Corresponding frequency (GHz) 2 5 7 9 10
[0100] Comparative Example 1
[0101] Comparative Example 1 differs from Example 1 in that the concentration of cellulose microfibers in the mixed dispersion in step (3) is changed, while other aspects remain the same:
[0102] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.05 wt.% cellulose nanofiber dispersion, and then completely frozen at -196℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0103] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0104] (3) Add silver nanowires with a weight ratio of 30% of cellulose microfibers to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse them into a uniform mixed dispersion. Then further dilute to obtain a mixed dispersion with a cellulose microfiber concentration of 1.0 wt.%.
[0105] (4) The mixed dispersion obtained in step (3) is completely frozen at -40°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0106] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0107] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 7). The cellulose-based aerogel has almost no elastic properties, produces a large strain loss at different strain amplitudes, and there is no significant difference in electromagnetic wave absorption performance at different strain amplitudes. The frequency at which the best electromagnetic wave absorption performance is obtained cannot cover multiple electromagnetic wave frequency bands.
[0108] Table 7. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0109] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 0 35 54 67 71 Optimum RL (-dB) 5 7 11 5 1 Corresponding frequency (GHz) 11 13 10 12 16
[0110] Comparative Example 2
[0111] Comparative Example 2 differs from Example 1 in that the complete freezing temperature of the mixed dispersion in step (4) is changed, while other aspects remain the same:
[0112] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.05 wt.% cellulose nanofiber dispersion, and then completely frozen at -196℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0113] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0114] (3) Add silver nanowires with a weight ratio of 30% of cellulose microfibers to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse them into a uniform mixed dispersion. Then further dilute to obtain a mixed dispersion with a cellulose microfiber concentration of 0.2 wt.%.
[0115] (4) The mixed dispersion obtained in step (3) is completely frozen at -196°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0116] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0117] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 8). The cellulose-based aerogel has almost no elastic properties, produces large strain loss at different strain amplitudes, and there is no significant difference in electromagnetic wave absorption performance at different strain amplitudes. The frequency at which the best electromagnetic wave absorption performance is obtained cannot cover multiple electromagnetic wave frequency bands.
[0118] Table 8. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0119] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 0 27 44 63 77 Optimum RL (-dB) 11 23 33 10 5 Corresponding frequency (GHz) 6 8 10 11 12
[0120] Comparative Example 3
[0121] Comparative Example 2 differs from Example 1 in that the complete freezing temperature of the mixed dispersion in step (4) is changed, while other aspects remain the same:
[0122] (1) The initial cellulose nanofiber dispersion was diluted with deionized water to a concentration of 0.05 wt.% cellulose nanofiber dispersion, and then completely frozen at -196℃ for the first freeze drying. The temperature of the cold well was -40℃ and the pressure was 10 Pa. Cellulose microfibers were obtained after freeze drying for 48 h.
[0123] (2) The cellulose microfibers obtained in step (1) are redispersed in deionized water to prepare a cellulose microfiber dispersion with a concentration of 1.0 wt.%.
[0124] (3) Add silver nanowires with a weight ratio of 30% of cellulose microfibers to the cellulose microfiber dispersion obtained in step (2) and ultrasonically disperse them into a uniform mixed dispersion. Then further dilute to obtain a mixed dispersion with a cellulose microfiber concentration of 0.2 wt.%.
[0125] (4) The mixed dispersion obtained in step (3) is completely frozen at -20°C and then subjected to a second freeze-drying, wherein the temperature of the cold well is -40°C and the pressure is 10Pa. After freeze-drying for 48 hours, cellulose-based aerogel is obtained.
[0126] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0127] The cellulose aerogel obtained in step (4) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 9). The cellulose-based aerogel exhibited moderate elastic properties and strain loss at different strain amplitudes, but the electromagnetic wave absorption performance varied at different strain amplitudes. Its dynamic adjustability based on strain amplitude was slightly weaker than that in Example 1.
[0128] Table 9. Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0129]
[0130]
[0131] Comparative Example 4
[0132] Comparative Example 4, compared to Example 1, directly prepared cellulose-based aerogels using nanofiber dispersions, with all other aspects remaining unchanged:
[0133] (1) Add silver nanowires at a weight ratio of 30 wt.% to cellulose nanofiber dispersion to cellulose nanofiber dispersion and ultrasonically disperse them into a uniform mixed solution. Then further dilute to obtain a mixed dispersion with a cellulose nanofiber concentration of 0.2 wt.%.
[0134] (2) The mixed dispersion obtained in step (1) is completely frozen at -40°C and then freeze-dried (the temperature of the cold well is -40°C and the pressure is 10Pa). After it is completely dried, cellulose-based aerogel is obtained.
[0135] Absorption performance of electromagnetic wave absorbing materials with dynamically adjustable strain amplitude:
[0136] The cellulose aerogel obtained in step (2) was subjected to stress-strain tests and strain loss calculations at different strain amplitudes using a universal testing machine. The electromagnetic wave absorption performance of the cellulose-based aerogel at different strain amplitudes was tested and calculated according to GJB / Z 158-2011 and GJB 5792-2006 (Table 10). The cellulose-based aerogel underwent structural collapse during freeze-drying, resulting in significant strain loss at different strain amplitudes. Furthermore, there was no significant difference in electromagnetic wave absorption performance at different strain amplitudes, and the frequency at which the best electromagnetic wave absorption performance was obtained could not cover multiple electromagnetic wave frequency bands.
[0137] Table 10 Strain loss and electromagnetic wave absorption properties of cellulose-based aerogels
[0138] Strain amplitude 0% 20% 40% 60% 80% Strain loss (%) 27 45 64 72 91 Optimum RL (-dB) 3 6 11 7 5 Corresponding frequency (GHz) Strain amplitude Strain loss (%) Optimum RL (-dB) Corresponding frequency (GHz) 6 8 5 7 9
[0139] Application examples
[0140] I. Innovative Applications in the Field of Smart Devices:
[0141] Adaptive electromagnetic compatibility smart terminal
[0142] Smart devices such as smartphones and wearables often face multi-band electromagnetic interference (e.g., frequency conflicts between 5G signals and Bluetooth / WiFi). A flexible electromagnetic shielding / absorption module is fabricated using cellulose-based aerogel as the core material. By controlling the strain on the material, the absorption frequency band can be dynamically switched (e.g., quickly switching from 2.4GHz (Bluetooth) to 3.5GHz (5G)). When the device detects strong electromagnetic interference in a certain frequency band, a built-in sensor triggers aerogel deformation (e.g., mechanical strain driven by a micro-motor), allowing it to accurately absorb the interference signal and ensuring the stable operation of core circuits (such as processors and sensors). Furthermore, the lightweight nature of aerogel can reduce the weight of the terminal, and its flexible structure is suitable for curved screens, foldable screens, and other designs, solving the problems of traditional metal shielding layers being "thick and rigid."
[0143] Wearable integrated electromagnetic protection and health monitoring device
[0144] For electromagnetically sensitive environments (such as near precision instruments in medical settings or high-voltage power grids), we are developing smart protective clothing based on cellulose-based aerogel. Its dynamically adjustable properties allow it to automatically adjust its absorption efficiency according to the intensity of surrounding electromagnetic radiation. Simultaneously, the aerogel's strain sensitivity enables health monitoring—minor deformations caused by human movement alter the aerogel's resistance, converting it into electrical signals that are transmitted to a terminal to monitor data such as step count and joint range of motion in real time, achieving a dual-function integration of protection and monitoring.
[0145] II. Strategic Applications in the Field of Military Equipment:
[0146] Synergistic effect of dynamic stealth and anti-jamming: The military scenario's requirements for "rapid response, wide-band adjustable, and precise countermeasure" of electromagnetic wave absorption are highly matched with the dynamic control characteristics of cellulose-based aerogels, which can significantly improve the survivability and combat capability of equipment.
[0147] Adaptive radar stealth equipment
[0148] Traditional stealth materials mostly absorb at fixed frequencies, making them ill-equipped to counter multi-band radar detection (such as meter-wave, microwave, and millimeter-wave). By using dynamically tunable cellulose-based aerogel as the core layer of a stealth coating, adaptive stealth is achieved through the following control methods: Strain control: A miniature hydraulic drive structure is designed on the surface of fighter jets and missiles. By changing the tensile / compressive deformation of the aerogel coating (strain range 0-50%), the electromagnetic parameters (such as dielectric loss and permeability) of its internal porous network are adjusted, allowing the absorption frequency band to be continuously tunable within the 1-40 GHz range. When enemy radar switches frequencies, the coating can respond within 0.1 seconds, increasing the reflection loss from -10 dB (90% absorption) to -40 dB (99.99% absorption), significantly reducing the radar cross-section (RCS).
[0149] Lightweight smart ammunition casing
[0150] A munition casing is fabricated using cellulose-based aerogel as the substrate and composited with high-temperature resistant ceramic particles. Its dynamically adjustable electromagnetic wave absorption properties play a dual role during munition flight: first, by sensing strain caused by air resistance, it adjusts the casing's radar wave absorption efficiency, thus evading detection by enemy air defense radar; second, before detonation, it rapidly switches to a low-absorption mode, ensuring that the electromagnetic triggering signal of the internal fuse (such as microwave detection for proximity fuses) is not interfered with, thereby improving accuracy. Furthermore, the lightweight nature of the aerogel reduces the munition's launch load, increasing range by approximately 15%, while its porous structure provides cushioning, enhancing the munition's shock resistance during transport and storage.
[0151] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.
Claims
1. A method for controlling the electromagnetic wave absorption performance of a material by controlling the strain amplitude, characterized in that, The process involves mixing a cellulose microfiber dispersion with a conductive / magnetic functional component, followed by complete freezing and then a second freeze-drying to obtain a cellulose-based aerogel. The electromagnetic wave absorption performance is then controlled by adjusting the strain amplitude of the cellulose-based aerogel.
2. The method according to claim 1, characterized in that, The method specifically includes the following steps: (1) The cellulose nanofiber dispersion was first completely frozen, and then freeze-dried to obtain cellulose microfibers; the obtained cellulose microfibers were dispersed in deionized water to obtain a cellulose microfiber dispersion. (2) The conductive / magnetic functional components are mixed with the above cellulose microfiber dispersion to form a mixed dispersion, then completely frozen and then freeze-dried a second time to obtain cellulose-based aerogel; (3) Electromagnetic wave absorption performance can be modulated by controlling the strain amplitude of cellulose-based aerogel.
3. A method for preparing a cellulose-based aerogel with dynamically tunable electromagnetic wave absorption properties, characterized in that, Includes the following steps: (1) The cellulose nanofiber dispersion was first completely frozen, and then freeze-dried to obtain cellulose microfibers; the obtained cellulose microfibers were dispersed in deionized water to obtain a cellulose microfiber dispersion. (2) Preparation of cellulose-based aerogel: The conductive / magnetic functional components are mixed with the above-mentioned cellulose microfiber dispersion, diluted to form a mixed dispersion, then completely frozen and then freeze-dried a second time to obtain cellulose-based aerogel.
4. The method according to any one of claims 1-3, characterized in that, The cellulose nanofibers described in step (1) are derived from one or more of bleached coniferous wood, broadleaf wood, bamboo pulp, cotton pulp, and hemp fiber, and are obtained through one or more processes such as TEMPO oxidation and mechanical grinding.
5. The method according to any one of claims 1-3, characterized in that, The cellulose nanofibers described in step (1) have any one of the following surface functional groups: carboxyl, amino, or phosphate.
6. The method according to any one of claims 1-3, characterized in that, The cellulose nanofibers described in step (1) have a diameter of 5-50 nm and a length of 10-100 μm.
7. The method according to any one of claims 1-3, characterized in that, The concentration of the cellulose nanofiber dispersion in step (1) is 0.05 wt.% to 0.5 wt.%.
8. The method according to any one of claims 1-3, characterized in that, The freezing temperature in step (1) is -196℃ to -20℃.
9. The method according to any one of claims 1-3, characterized in that, The concentration of the cellulose microfiber dispersion in step (1) is 0.05 wt.% to 2 wt.%.
10. The method according to any one of claims 1-3, characterized in that, In step (2), the conductive functional component is one or more of the following: carbon black, carbon quantum dots, carbon nanotubes, MXene, graphene, fullerene, and nano-metals.
11. The method according to any one of claims 1-3, characterized in that, In step (2), the magnetically conductive functional component is one or more of ferrite, metallic magnetic alloy, metallic nanoparticles, magnetic oxide nanoparticles, and topological insulators.
12. The method according to any one of claims 1-3, characterized in that, The conductive / magnetic functional component described in step (2) has a mass ratio of 1 wt.% to 50 wt.% relative to the microfibers in the solution.
13. The method according to any one of claims 1-3, characterized in that, The concentration of cellulose microfibers in the mixed dispersion described in step (2) is 0.1 wt.% to 2 wt.%.
14. The method according to any one of claims 1-3, characterized in that, The freezing temperature in step (2) is -196℃ to -40℃.
15. A cellulose-based aerogel with dynamically adjustable electromagnetic wave absorption properties prepared by the method according to any one of claims 3-14.
16. The application of the cellulose-based aerogel of claim 15 in smart devices.
17. The use of the cellulose-based aerogel of claim 15 in military equipment.
18. The application of the cellulose-based aerogel according to claim 15 in the field of mobile communications.
Citation Information
Patent Citations
Bamboo fiber-based electromagnetic wave absorbing material and preparation method thereof
CN119012665A